Identifikasi Spesies Lamun di Wilayah Perairan Teluk Saleh Kabupaten Sumbawa - Lala Dwi Sasmitha; Sutarno; Suratman (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify seagrass species found in the waters of Saleh Bay, Sumbawa Regency, and analyze the phylogenetic relationships between species based on morphological characteristics using a phenetic approach. The research was conducted from May to July 2025 at two observation stations, namely Gili Rakit and Gili Bakau. Sampling was carried out using purposive sampling with line transects, while species identification was based on observations of morphological characteristics including shape, size, leaf color, leaf tip and edge shape, root structure, and the presence of stem hairs. Morphological data were analyzed descriptively and then used in kinship relationship analysis using NTSYS version 2.02 software to produce a phenetic dendrogram. The results showed that five seagrass species were identified, namely Oceana serrulata, Cymodocea rotundata, Halodule uninervis, Halophila major, and Enhalus acoroides. Phenetic analysis showed consistent grouping between replicates within a species with a high degree of similarity, as well as clear separation of clusters between species. Oceana serrulata and Cymodocea rotundata show the closest kinship, while Enhalus acoroides is in the most separate cluster. These results indicate that morphological identification combined with phenetic analysis is effective in describing seagrass diversity and phylogenetic relationships, and can serve as an important basis for seagrass ecosystem management and conservation efforts in the waters of Saleh Bay.